2014
DOI: 10.5604/17322693.1101229
|View full text |Cite
|
Sign up to set email alerts
|

Interferons: between structure and function

Abstract: Interferons are a family of proteins that are released by a variety of cells in response to infections caused by viruses. Currently, we distinguish three types of interferons. They are classified based on the nucleotide sequence, interaction with specific receptors, chromosomal location, structure and physicochemical properties. The following interferons are classified as type I: α, β, ω, κ, ε, ζ, τ, δ, ν. They are recognized and bound by a receptor formed by two peptides, IFN-αR1 and IFN-αR2. Representative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…It has been reported that IFN-γ in mammals can prevent the infiltration and destruction of virions in cells during virus infection, as well as the formation of virions or germination of viruses. It can further stimulate cells of the immune system to protect the human body [72]. Kidane et al reported that in vitro attenuated Histomonas meleagridis vaccination results in high levels of IFN-γ in the cecum of turkeys, which might involve important mechanisms of immune responses against avian diseases [71].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IFN-γ in mammals can prevent the infiltration and destruction of virions in cells during virus infection, as well as the formation of virions or germination of viruses. It can further stimulate cells of the immune system to protect the human body [72]. Kidane et al reported that in vitro attenuated Histomonas meleagridis vaccination results in high levels of IFN-γ in the cecum of turkeys, which might involve important mechanisms of immune responses against avian diseases [71].…”
Section: Discussionmentioning
confidence: 99%
“…It is divided into three types: α, β and γ. Many studies have shown that interferon (especially α-interferon and γinterferon) has an obvious anti-cell proliferation effect [46]. Therefore, low-risk patients have a better prognosis and reduce mortality through these immune response and in ammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…At present, two types of drug are utilized for HBV treatment, including nucleoside analogues and interferon (IFN)-α) and its derivatives ( 4 ). IFNs are cytokines that exhibit anti-proliferative, antiviral and immunomodulatory activities ( 5 , 6 ). Furthermore, IFN-α serves a key role in the inhibition of viral replication ( 7 ).…”
Section: Introductionmentioning
confidence: 99%